Investigating how health apps influence college students’ health behavior - Kamanga, Ursula (Kansas State University, 2016)
This study examined how health apps influence college students’ health behavior, because about 50 percent of college students do not comply with physical activity recommendations. Because mobile applications (apps) are popular among college students, they hold promise for promoting behavior change in physical activity. This research was conducted through an online questionnaire distributed to a randomized sample of 18-35 year-old Mid-Western university students. Questionnaire data were analyzed from 237 surveys using Pearson’s Product Moment correlation (r) and Pearson’s chi-square test (χ2). This study showed that college students generally perceived health apps to be useful with slightly over half of the participants using health apps (52.3 percent). Bivariate analysis indicated positive attitudes towards health apps and positive attitudes towards physical activity (p < .001). The amount of experience using health apps yielded a positive relationship with attitudes towards physical activity (p = .008). In addition, having strong beliefs towards physical activity indicated a positive correlation with engaging in physical activity (p < .001). This study provides valuable information regarding attitudes towards health apps and the intention to use health apps for physical activity. While health apps do not trigger an intention to do physical activity, having “belief strength” and positive attitudes towards physical activity increases the likelihood for engaging in physical activity. Health communication intervention strategies and health practitioners can use this information to educate individuals about the advantages for their health that can be associated with using health apps.
Keywords: Health apps; College students; Motivation; Physical activity; Technology; Mobile devices